The Thirteenth Knight - Quinn, Jordan (Quinn, Jordan. Kingdom of Wrenly, 2018)
Clara, Tublock, and many others compete to become one of the ultimate defenders of the Kingdom of Wrenly, a member of the elite Knight Spires.